Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Check my answer!

Write the product as a trinomial.

(m - 6)(m + 3)

My answer: m^2 - 9m + 18


Sagot :

[tex] (m - 6)(m + 3)=\\ m^2+3m-6m-18=\\ m^2-3m-18[/tex]
m x m  =  m ^ 2
m x 3 =    3m
-6 x m =   -6m
-6 x 3 =    -18

adding these you get    m^2 -3m -18